Galectin-9 restricts hepatitis B virus replication via p62/SQSTM1-mediated selective autophagy of viral core proteins - Miyakawa, Kei; Nishi, Mayuko; Ogawa, Michinaga; Matsunaga, Satoko; Sugiyama, Masaya; Nishitsuji, Hironori; Kimura, Hirokazu; Ohnishi, Makoto; Watashi, Koichi; Shimotohno, Kunitada; Wakita, Takaji; Ryo, Akihide (Nature communications, 2022)
Autophagy has been linked to a wide range of functions, including a degradative process that defends host cells against pathogens. Although the involvement of autophagy in HBV infection has become apparent, it remains unknown whether selective autophagy plays a critical role in HBV restriction. Here, we report that a member of the galectin family, GAL9, directs the autophagic degradation of HBV HBc. BRET screening revealed that GAL9 interacts with HBc in living cells. Ectopic expression of GAL9 induces the formation of HBc-containing cytoplasmic puncta through interaction with another antiviral factor viperin, which co-localized with the autophagosome marker LC3. Mechanistically, GAL9 associates with HBc via viperin at the cytoplasmic puncta and enhanced the auto-ubiquitination of RNF13, resulting in p62 recruitment to form LC3-positive autophagosomes. Notably, both GAL9 and viperin are type I IFN-stimulated genes that act synergistically for the IFN-dependent proteolysis of HBc in HBV-infected hepatocytes. Collectively, these results reveal a previously undescribed antiviral mechanism against HBV in infected cells and a form of crosstalk between the innate immune system and selective autophagy in viral infection. In human cells, invading pathogens trigger an innate immune response that helps prevent viral replication and spread. Here, the authors reveal a mechanism of innate immunity that selectively leads to the autophagic degradation of hepatitis B virus core protein.